2017
DOI: 10.1021/acs.jpclett.6b02773
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Multiconfigurational States of Hydrogen-Passivated Silicene Nanoclusters

Abstract: Utilizing density functional theory (DFT) and a complete active space self-consistent field (CASSCF) approach,we study the electronic properties of rectangular silicene nano clusters with hydrogen passivated edges denoted by H-SiNCs (n,n), with n and n representing the zigzag and armchair directions, respectively. The results show that in the n direction, the H-SiNCs prefer to be in a singlet (S = 0) ground state for n > n. However, a transition from a singlet (S = 0) to a triplet (S = 1) ground state is revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…We also ran complete active-space self-consistent field (CASSCF) calculations of the charged molecules of the corresponding electronic multiplicity also using the B3LYP functional to explore their multi-configurational character. This is due to correct and compare, if needed, for the multi-configurational character of the neutral H-SiNCs reported in a previous study [8] at the B3LYP level of theory. The chosen active spaces consisted of 9 electrons and 10 orbitals, and 11 electrons and 10 orbitals, for cation and anion radicals, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…We also ran complete active-space self-consistent field (CASSCF) calculations of the charged molecules of the corresponding electronic multiplicity also using the B3LYP functional to explore their multi-configurational character. This is due to correct and compare, if needed, for the multi-configurational character of the neutral H-SiNCs reported in a previous study [8] at the B3LYP level of theory. The chosen active spaces consisted of 9 electrons and 10 orbitals, and 11 electrons and 10 orbitals, for cation and anion radicals, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The geometry optimizations and properties calculations were performed using D3BJ dispersion-corrected TPSS in combination with def2-SVP basis set in Turbomole v7.3 25 and Gaussian 16 revision A3 26 codes. In previous studies, 27 it was demonstrated that the basis set def2-SVP yields good results for this kind of system without compromising the computational cost. The frequency calculates were run for all studied systems to ensure that a minimum (no imaginary frequencies) have been located.…”
Section: Computational Detailsmentioning
confidence: 94%
“…Other elements such as silicon and phosphorus are also known to form 2D structures, therefore, the electronic properties of rectangular silicene nano clusters (nanoflakes) with hydrogen passivated edges with two zigzag and two armchair edges have been explored (Pablo-Pedro et al, 2017).…”
Section: Silicene Nanoflakesmentioning
confidence: 99%